A positive relationship between weight-adjusted waist index and non-alcoholic fatty liver disease: a study on US adolescents - Xiaoling Cui; Xiaoling Cui; Yize Huang; Luyang Kang; Lianxiu Han; Weijie Sun; Kexing Han; Yufeng Gao (Frontiers in Medicine)
BackgroundNon-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver condition in children, underscoring the urgent need for non-invasive markers for early detection in this population.MethodsWe utilized survey data from the National Health and Nutrition Examination Survey (NHANES) 2017–2020 regarding liver ultrasound transient elastography (LUTE) for the diagnosis of NAFLD (dependent variable), and used multiple logistic regression models to explore the association between weight-adjusted waist circumference index (WWI) and the prevalence of NAFLD in US adolescents. Smoothing curves and threshold effect analyses were used to assess the non-linear association between the independent variables and the dependent variable. Subgroup analysis was conducted to pinpoint particularly susceptible subgroups within our study cohort of 1,711 participants.ResultsOur findings indicated a positive correlation between WWI and NAFLD scores. Adjusting for all covariates revealed a significant association between increased WWI and the presence of NAFLD, with an odds ratio of 3.37 (95% CI: 2.74, 4.15). This association proved stronger than those observed with waist circumference, body mass index, and NAFLD. Stratifying WWI into quartiles showed a clear and strong positive correlation (P for trend < 0.0001). The results of smoothing curves and threshold effect analysis showed a non-linear relationship between WWI and NAFLD (LLR < 0.001). Notably, for WWI values below 10.65, a significant correlation was observed (OR = 5.25, 95% CI: 3.77,7.31). Additionally, our subgroup analysis revealed that WWI and NAFLD were associated more positively among male participants aged 16 years and older.ConclusionWWI is positively correlated with NAFLD in American adolescents and offers a straightforward and cost-effective method for identifying hepatic steatosis. The findings highlight the importance of focusing on individuals with a WWI below 10.65, where the risk of NAFLD increases. Priority should be given to the male adolescent population aged 16 and above.